The Flow Rate Characteristics of CO Gas Emissions Using Simflow 3.1 - Febriyani, Eka; Hidayati, Nuroh (Computational And Experimental Research In Materials And Renewable Energy, 2020)
Carbon monoxide (CO) is a type of pollutant produced by industrial activities and is emitted through gas exhaust flues. Simulation activities are considered to provide a lot of information regarding the distribution of CO gas flow in the air. This paper will analyze the velocity and pressure distribution characteristics of CO gas to predict the accumulation of CO gas at various variations in the distribution distance of the gas. Simulation activities are carried out using SIMFLOW 3.1, a software capable of simulating fluid dynamics by emphasizing the ease of application. The simulation results show that the flow rate of CO gas is proportional to the amount of gas pressure generated at each distribution distance of the gas. The CO gas flow shows a fairly stable movement when identified at a distance of more than 30 m. This indicates that a mass of CO gas will be transmitted in the same amount over a distance of up to 70 m. The largest gas accumulation was obtained at a distance of 20 m from the source, which was indicated by the smallest gas flow velocity of 3.87 x 10-3 m/s.